THE EFFECTIVENESS OF YOUTUBE ANIMATION VIDEOS TO IMPROVE STUDENTS' VOCABULARY MASTERY - Pramesti, Corry Evalyna; Ningrum, Yusnita Sylvia (Universitas Muhammadiyah Metro, 2025)
Vocabulary plays an important role in language learning. Vocabulary mastery is paramount in learning English because it can improve language skills. However, problems in vocabulary learning can still be found among junior high school students in Indonesia. This study aims to determine the effectiveness and significant differences in the use of YouTube animated videos to improve students' vocabulary mastery. This study is a quantitative research method with a quasi-experimental design that involves grade VIII students of SMPN 1 Madukara. This research instrument is in the form of a multiple-choice test of 35 questions that measure students' vocabulary mastery of verbs and adjectives. Data were obtained by giving pre-tests and post-tests to the control and experimental groups. The results of this study show that YouTube animated videos are not effective in improving vocabulary mastery. The experimental group obtained an average score of 87.24 and the control group obtained a score of 83.84. Meanwhile, the results of student scores in the experimental group before and after treatment showed significant differences. Initially, the average score of the student was 72.92, but after treatment, the score increased to 87.24. It can be concluded that although the score of the experimental group was higher than the score of the control group, the results were insignificant and the use of YouTube animated videos was less effective in improving vocabulary mastery. However, this learning media significantly affects students' vocabulary scores. Therefore, YouTube animated videos can be used for vocabulary learning because they can improve student scores and serve as an alternative to monotonous traditional learning media. These findings also imply that teachers can use morally charged YouTube animated videos as an engaging and contextual support medium to improve vocabulary learning in the classroom.